A Healthier Balance of Expertise: An Innovative Model for Community-University Alliances in Health Research - Crewe, Carolina; Clow, Barbara (Atlantis, 2008)
As a research model, the Healthy Balance Research Program stands as a successful alliance between researchers, community organizations and policymakers. Its advisory bodies (equity-seeking populations and policymakers) provide checks and balances to traditional academic research structures, and overall help ensure information uptake and community engagement with unpaid caregivers in Nova Scotia.